2010
DOI: 10.1016/j.firesaf.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental review of the homogeneous temperature assumption in post-flashover compartment fires

Abstract: Traditional methods for quantifying and modelling compartment fires for structural engineering analysis assume spatially homogeneous temperature conditions. The accuracy and range of validity of this assumption is examined here using the previously conducted fire tests of Cardington (1999) and Dalmarnock (2006). Statistical analyses of the test measurements provide insights into the temperature field in the compartments. The temperature distributions are statistically examined in terms of dispersion from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…This hypothesis has recently been tested. The results of this work demonstrate that uniform temperature conditions are not present and large variation exists [32].…”
Section: The Firementioning
confidence: 77%
“…This hypothesis has recently been tested. The results of this work demonstrate that uniform temperature conditions are not present and large variation exists [32].…”
Section: The Firementioning
confidence: 77%
“…Stern-Gottfried et al [19] have reviewed this assumption by analysis of existing experimental data from well-instrumented fire tests. Results show that dispersion from the spatial compartment average is significant and that the assumption of uniform temperature conditions does not hold well.…”
Section: Limitations Of the Uniform Burning Assumptionmentioning
confidence: 99%
“…The well instrumented tests conducted at Dalmarnock [24] and Cardington [25] were shown to have large standard deviations (in excess of 200°C at times) within the temperature field [19]. Additionally, peak local temperatures in these tests were found to vary from 23% to 75% above the compartment spatial averages, and local minimums ranged from 29% to 99% below the averages.…”
Section: Limitations Of the Uniform Burning Assumptionmentioning
confidence: 99%
“…Nonetheless, the most important shortcoming of these methods is the assumption of uniform burning and homogenous compartment temperature regardless of the compartment size Rein, 2012a, 2012b) as it is shown that temperature conditions are non-uniform in most compartments (Stern-Gottfried et al, 2010b). Tests have also shown that there is a high degree of temperature variations even within small compartments (Stern-Gottfried et al, 2010a;Welch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%